Analysis Use Sundanese Among Teenagers In Pasauran Village In The Era Globalization - Riska Noviana; Rieska Amelia; Suhawati Perdana Putri; Eneng Liah Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2024)
Regional languages, such as Sundanese, are an important part of the cultural identity that shapes the selfhood of a community. However, in the era of globalization, the use of Sundanese among the younger generation faces significant challenges. This study aims to analyze the use of Sundanese in Kampung Pasauran, Banten, in the context of social change and the dominance of national and international languages. Using a qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis. The respondents consisted of youth aged 15-19 years who were purposively selected. The results show that Sundanese is increasingly rarely used by youth in daily life, with most respondents preferring Indonesian or a mix of Sundanese and Indonesian. Factors influencing this shift include the perception that Sundanese is less modern, the dominance of digital media that promotes the use of Indonesian and English, and the perceived difficulty of learning Sundanese. However, all respondents reported understanding and being able to speak Sundanese, albeit only in limited contexts, such as communication with parents or older relatives. This study underscores the importance of efforts to preserve Sundanese, particularly through education and the strengthening of cultural identity among the younger generation, to prevent further decline in its usage.